Statistics for Economics - Naghshpour, Shahdad (Business Expert Press, 2012)
Ebook from IG Library ; Statistics is the branch of mathematics that deals with real life problems. As such, it is an essential tool for economists. Unfortunately, the way the concept is introduced to students is not compatible with the way the economists think and learn. The problem is worsened by the use of mathematical jargon and complex derivations. However, as this book demonstrates, neither is necessary. The book is written in simple English with minimal use of symbols. All the examples and exercises in the book are constructed within the field of economics, thus eliminating the difficulty of learning statistics with examples from fields that have no relation to business, politics, or policy. Statistics is not more difficult than economics. Anyone that can comprehend economics can understand and use statistics successfully. The book utilizes Microsoft Excel to obtain statistical results, as well as to perform additional necessary computations. Although the Excel spreadsheet is not the software of choice for performing sophisticated statistical analysis, it is widely available and almost everyone has some degree of familiarity with Excel.